x+4=2(x+1)

Simple and best practice solution for x+4=2(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+4=2(x+1) equation:



x+4=2(x+1)
We move all terms to the left:
x+4-(2(x+1))=0
We calculate terms in parentheses: -(2(x+1)), so:
2(x+1)
We multiply parentheses
2x+2
Back to the equation:
-(2x+2)
We get rid of parentheses
x-2x-2+4=0
We add all the numbers together, and all the variables
-1x+2=0
We move all terms containing x to the left, all other terms to the right
-x=-2
x=-2/-1
x=+2

See similar equations:

| -3=3(3x-4) | | 6a-5=47 | | 5x–25=0 | | 8x=3x+4 | | 12/5x=27/10 | | 33=17+8a | | 7-2(2x-1)=x-5= | | 15-3x+4=2x-1+5x | | –2x+9=–3x+1 | | 1,6666666666666+y=2,75 | | 7x+6=6x–5 | | 5t-8=3t-5 | | 1+2/3+y=2+3/4 | | 6x+68=10x-8 | | 6+7=-48-5x | | 2(x+4)+5x(x+4)=0 | | 3(4p-2)=2(3p-12) | | 5x=15/16 | | 20+2x-1+51=180 | | 3(2p-6)=6(4p+15) | | 10-3x=4+2x | | 6(x-4)+3(x-7)=3 | | –(u−–4)=–10 | | 3(2n+4)=2(4n+3) | | 3(f-4)=0 | | 7=q2− –6 | | 8(a+6)=6(a+12) | | y=-2*10^-07*500^2+0.0006*500 | | 8x−2x+–11x+–9x=–14 | | 6(y+4)=5(y+6) | | y=-2^-07*500^2+0.0006*500 | | 12y-10=50 |

Equations solver categories